2016
DOI: 10.5539/ass.v12n12p251
|View full text |Cite
|
Sign up to set email alerts
|

Media Usage Patterns among Chinese Voters: In Preparation for the 14th Malaysian General Election (GE14)

Abstract: The growing popularity of networked media has given opportunities for the people in this democratic society to search for diverse information and compare information with other sources of information, thereafter making their choice to whom they want to elect and to which information they think is reliable. Notwithstanding the influential power of networked media in elections, among people who have access to this media, there are still people who just rely on traditional media or use both at the same time for i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Because most of the previous research very much focusing on the impact of Facebook (Chang & Tham, 2016;Leng Ho, 2012) and Twitter (Faizal Kasmani, Sabran, & Adzrah Ramle, 2014;Rosyidah Muhamad, 2015) on electoral results in Malaysia, this study, however, will discuss on the impact of WhatsApp on elections outcome. Therefore, this study is to embark on the influencing factor of WhatsApp in political marketing and party campaigning strategy in the wake of GE 14.…”
Section: Introductionmentioning
confidence: 99%
“…Because most of the previous research very much focusing on the impact of Facebook (Chang & Tham, 2016;Leng Ho, 2012) and Twitter (Faizal Kasmani, Sabran, & Adzrah Ramle, 2014;Rosyidah Muhamad, 2015) on electoral results in Malaysia, this study, however, will discuss on the impact of WhatsApp on elections outcome. Therefore, this study is to embark on the influencing factor of WhatsApp in political marketing and party campaigning strategy in the wake of GE 14.…”
Section: Introductionmentioning
confidence: 99%
“…Acknowledging the overwhelming growth of networked media and technological changes in information delivery systems such as the Internet and social media in providing valuable information to the public especially during the general election, Malaysians consumed "a lot more" news and information than before. The proliferation of social media has allowed searching for diverse information and thereafter make their choice to which information they think is reliable (Chang and Tham, 2016). The notable social media such as Facebook, Instagram, WhatsApp, Twitter, YouTube and blog, are among the most used, regardless of frequency.…”
Section: Introductionmentioning
confidence: 99%
“…The notable social media such as Facebook, Instagram, WhatsApp, Twitter, YouTube and blog, are among the most used, regardless of frequency. Chang and Tham (2016) found that social media especially Facebook was the prominent communication and entertainment tool as well as the source of information used by the majority of Chinese informants from the seven states in Malaysia. However, the majority of informants in the study also concurred that they are still using traditional media for information seeking mainly because they are concerned about the reliability and validity of news on social media, especially on Facebook.…”
Section: Introductionmentioning
confidence: 99%